Lussazioni interfalangee e metacarpofalangee - Anania, V.; Chinni, C. (Lo Scalpello - Journal, 2018)
INTERPHALANGEAL AND METACARPOPHALANGEAL DISLOCATION OF FINGERSThe term “dislocation” refers to the loss of contact of the articular surfaces of the phalanx joints. Very often thedislocation of a phalange is accompanied by injuries and involvement of the structures of adjacent soft tissues. Theseinjuries are extremely common in those who practice sport and, in particular, in those sports activities that provide foranomalous and thraumatic contacts with a ball or contrasts with an opponent. In this short treatment we willexamine the common joint dislocations interphalangeal and metacarpophalangeal of the fingers of the hand. Forwhat concerns the pathology of the first finger, there is a great number of important lesions associated as fractures orlesions of ligaments (Stener); given the vastness and complexity of these diseases, that would require a separatetreatment, we will confine ourselves to describing the “simple” dislocations of the first finger.